An epoxide hydrolase from endophytic Streptomycess hows unique structural features and wide biocatalytic activity - Tormet-Gonzalez, Gabriela D.; Wilson, Carolina [UNESP]; Oliveira, Gabriel Stephani de; Santos, Jademilson Celestino dos; Oliveira, Luciana G. de; Dias, Marcio Vinicius Bertacine [UNESP] (Int Union Crystallography, 2020)
The genusStreptomycesis characterized by the production of a wide variety of secondary metabolites with remarkable biological activities and broad antibiotic capabilities. The presence of an unprecedented number of genes encoding hydrolytic enzymes with industrial appeal such as epoxide hydrolases (EHs) reveals its resourceful microscopic machinery. The whole-genome sequence ofStreptomycessp. CBMAI 2042, an endophytic actinobacterium isolated fromCitrus sinensisbranches, was explored by genome mining, and a putative alpha/beta-epoxide hydrolase named B1EPH2 and encoded by 344 amino acids was selected for functional and structural studies. The crystal structure of B1EPH2 was obtained at a resolution of 2.2 angstrom and it was found to have a similar fold to other EHs, despite its hexameric quaternary structure, which contrasts with previously solved dimeric and monomeric EH structures. While B1EPH2 has a high sequence similarity to EHB fromMycobacterium tuberculosis, its cavity is similar to that of human EH. A group of 12 aromatic and aliphatic racemic epoxides were assayed to determine the activity of B1EPH2; remarkably, this enzyme was able to hydrolyse all the epoxides to the respective 1,2-diols, indicating a wide-range substrate scope acceptance. Moreover, the (R)- and (S)-enantiomers of styrene oxide, epichlorohydrin and 1,2-epoxybutane were used to monitor enantiopreference. Taken together, the functional and structural analyses indicate that this enzyme is an attractive biocatalyst for future biotechnological applications.
Keywords: epoxide hydrolases; alpha/beta-hydrolases; biocatalysis; Streptomyces